2023
DOI: 10.3390/biomedicines11051340
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Modulates Efficacious Changes in the Immune Response against Tuberculosis

Abstract: Glutathione (GSH) is an antioxidant in human cells that is utilized to prevent damage occurred by reactive oxygen species, free radicals, peroxides, lipid peroxides, and heavy metals. Due to its immunological role in tuberculosis (TB), GSH is hypothesized to play an important part in the immune response against M. tb infection. In fact, one of the hallmark structures of TB is granuloma formation, which involves many types of immune cells. T cells, specifically, are a major component and are involved in the rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Glutathione's support of immune system function extends to its influence on T-cell lymphocytes, pivotal players in the immune response, and its control over free radicals essential for inflammatory processes [ 23 ]. In the immune response against tuberculosis, glutathione emerges as a critical regulator, impacting the activation, metabolism, cytokine release, redox activity, and free radical levels of macrophages, natural killer cells, and T cells [ 24 ]. Maintaining optimal glutathione levels proves crucial for enhancing immune responses against tuberculosis infection, thereby improving outcomes for patients with heightened susceptibility, such as those with HIV or type 2 diabetes [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione's support of immune system function extends to its influence on T-cell lymphocytes, pivotal players in the immune response, and its control over free radicals essential for inflammatory processes [ 23 ]. In the immune response against tuberculosis, glutathione emerges as a critical regulator, impacting the activation, metabolism, cytokine release, redox activity, and free radical levels of macrophages, natural killer cells, and T cells [ 24 ]. Maintaining optimal glutathione levels proves crucial for enhancing immune responses against tuberculosis infection, thereby improving outcomes for patients with heightened susceptibility, such as those with HIV or type 2 diabetes [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…In essence, glutathione serves as a vital immunomodulatory antioxidant by stabilizing redox activity, steering cytokine profiles toward a beneficial immune response, and augmenting the function of T lymphocytes [ 24 ]. This underscores the profound significance of glutathione in modulating immune cell function and bolstering immune responses in diverse infectious and inflammatory conditions, highlighting its potential as a therapeutic target for enhancing host defenses.…”
Section: Reviewmentioning
confidence: 99%
“…In addition to excessive amounts of free radicals found when GSH is low, we see excessive inflammation marked by increased levels of IL-1, IL-6, and TNF-α [ 9 ]. The increase in pro-inflammatory cytokines reciprocally amplifies the production of oxygen radicals, which are scavenged by free GSH, creating a cycle where low GSH levels contribute to both increased inflammation and free radical production.…”
Section: Glutathione: Inflammation and Immune Responsementioning
confidence: 99%
“…In the context of the immune system, optimal glutathione levels are essential for the maintenance of a redox-balanced environment for the proper functioning of lymphocytes and macrophages [ 6 , 7 ]. Previous studies have shown that glutathione supplementation can modulate the cellular redox status for an improved immune response against infectious pathogens, notably Mycobacterium tuberculosis [ 8 , 9 ]. Deficiencies in glutathione have been associated with impaired immune function and increased susceptibility to various diseases, particularly in Individuals with HIV [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…GSH plays a crucial role in maintaining normal immune system function, while possessing antioxidant and detoxification properties 57 . The thiol group on cysteine, known as G‐SH, serves as the active moiety and can bind to drugs, toxins, and other substances, facilitating detoxification 58 …”
Section: Metabolic Pathways Alterationsmentioning
confidence: 99%